Could the impact of a public policy help us evaluate the changes that have been implemented? An analysis of non-take-up of Spanish minimum income schemes - Diego Mu\~noz-Higueras; Rafael Granell; Amadeo Fuenmayor Fernández (Review of Economic Analysis (REA), 2023)
This paper provides new evidence on why people who are eligible to receive a benefit do not apply for it, an occurrence most commonly referred to as 'non-take-up'. It examines the relationship between the characteristics of the Guaranteed Minimum Income (GMI) and the non-take-up rate achieved by these benefits. This study looks into five main causal conditions in the design of a GMI: the amount of the benefit, the duration of the benefit, the administration's resolution times, the documentation requirements and an aggregation of supply side factors. The sample used corresponds to the 19 existing regional GMI programmes in Spain. The existence of relationships between causal conditions is tested using the Fuzzy-set Qualitative Comparative Analysis (FsQCA) methodology. The results show that there are three different combinations of conditions that result in less than 45% coverage of a GMI. With these results it is possible to evaluate ex ante whether the Spanish Minimum Vital Income (MVI) can avoid the non-take-up problem that other GMIs have in Spain. We find that the new MVI does not follow any of the combined conditions that lead to the failings of the GMI's coverage rate.
Keywords: C11; D04; E6; H43; H50; 330; Non-take-up; Coverage; Fuzzy-set QCA; Minimum Income; Minimum Vital Income; Public Policy Evaluation